Negative Requests Within Hair Salons: Grammar and Embodiment in Action Formation - Horlacher, Anne-Sylvie (Frontiers in Psychology, 2022)
Although requests constitute a type of action that have been widely discussed within conversation analysis-oriented work, they have only recently begun to be explored in relation to the situated and multimodal dimensions in which they occur. The contribution of this paper resides in the integration of bodily-visual conduct (gaze and facial expression, gesture and locomotion, object manipulation) into a more grammatical account of requesting. Drawing on video recordings collected in two different hair salons located in the French-speaking part of Switzerland and in France (23 h in total), this paper analyzes clients’ negative requests by exploring how they interface with the participants’ embodied conducts. Contrary to what the literature describes for positively formulated requests, with negative requests clients challenge an expectable next action (or ongoing action) by the hairdresser. One linguistic format constitutes the focus of this article, roughly glossable as ‘You don’t do [action X] too much (huh)’. Our analysis of a consistent collection of such formatted turns will show that clients present them (and hairdressers tend to treat them) in different ways, depending on how they relate to embodied conduct: When these turns are used by the client as instructions, they are accompanied by manipulations of the client’s own hair and tend to occur toward the initial phase of the encounter, at a stage when hairdressers and clients collaboratively negotiate the service in prospect. When uttered as directives, these turns are not accompanied by any touching practices from the client and are typically observable in subsequent phases of the encounter, making relevant an immediate linguistic or/and bodily response from the professional, as shown by the client who is actively pursuing mutual gaze with him/her. Therefore, an action cannot be distinguished from another on the basis of the turn format alone: Its sequential placement and the participants’ co-occurring embodied conduct contribute to its situated and shared understanding. By analyzing the clients’ use of a specific linguistic format conjointly with the deployment of specific embodied resources, this study will advance our understanding of how verbal resources and embodiment operate in concert with each other in the formation and understanding of actions, thereby feeding into new areas of research on the grammar-body interface.